The Influence of Integrated Marketing Communication Models on Deep Customer Engagement Creation - Tammayattiwong, Sirikarn; Mueandecha, Thidarat; Uppapong, Kullaya (Journal of Posthumanism, 2025)
The intense competitive landscape presents consumers with a wide variety of brands to choose from. Marketing communication serves as a crucial tool for creating brand awareness and recognition, ultimately influencing purchasing decisions. Moreover, this approach plays a significant role in fostering deep customer engagement. The objective of this research is to examine an integrated marketing communication model that enhances deep customer engagement. A mixed-method research approach was employed, using an Exploratory Sequential Design, which gives equal emphasis to both qualitative and quantitative research (Equivalent Status Design).For the qualitative research, the target group consisted of 12 executives and managers from CP All Public Company Limited and branch managers of 7-Eleven stores. Structured interviews were used as the research instrument. In the quantitative research phase, the population included 490 consumers who had purchased products or used services from 7-Eleven stores in Bangkok and its metropolitan area. A systematic random sampling method was used to select 82 respondents, and data was collected via questionnaires. The data was analyzed using Structural Equation Modeling (SEM) with the AMOS software. The findings indicate that the integrated marketing communication model positively influences deep customer engagement. Among the direct influencing factors, social media customer relationship management had the strongest impact, followed by intensive engagement and integrated marketing communication. Additionally, the model exerted an indirect influence on deep customer engagement through social media customer relationship management and intensive engagement. Among these indirect influences, intensive engagement emerged as the strongest mediating variable, highlighting the critical role in fostering deep customer connections.